Inkonsistensi Politik Hukum dalam Ratifikasi Perjanjian Internasional di Indonesia - Fajrin, Fera Wulandari; Larasati, Kandi Kirana; Jamaluddin, Fitriani (Jurnal Risalah Hukum, 2025)
The legal binding of a country to an internationally agreed treaty to be implemented in the national law of that country is through ratification. The implementation of ratification should be carried out consistently, based on national interests, legal certainty, constitutional mandates, and the welfare of the general public. This research is a normative legal study with an approach through analysis of primary law and the use of secondary law. The results of this study show that in practice, Indonesia demonstrates an inconsistent attitude towards ratifying international agreements, where the Indonesian government can ratify an international agreement quickly if it supports the government's economic or political interests, but delays or even avoids it if it is considered sensitive or puts pressure on its power, even though the agreement concerns public interests such as human rights, the environment, or the livelihood of many people. Thus, there is a need for national legal political reform through regulatory revisions, setting deadlines for ratification, establishing annual priority agendas, mandatory public reporting on delays, and involving civil society and academics. This reform also needs to be supported by the formation of a cross-sector team tasked with overseeing the ratification process in an inclusive and strategic manner